Ipilimumab and Gemcitabine for Advanced Pancreatic Cancer: A Phase Ib Study. (19th November 2019) - Kamath, Suneel D.; Kalyan, Aparna; Kircher, Sheetal; Nimeiri, Halla; Fought, Angela J.; Benson, Al; Mulcahy, Mary
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) remains resistant to chemotherapy and immunotherapy individually because of its desmoplastic stroma and immunosuppressive tumor microenvironment. Synergizing cytotoxic T‐lymphocyte–associated antigen 4 (CTLA‐4) immune checkpoint blockade with chemotherapy could overcome these barriers. Here we present results of a phase Ib trial combining ipilimumab and gemcitabine in advanced PDAC. Materials and Methods: This was a single‐institution study with a 3 + 3 dose‐escalation design. The primary objective was to determine the maximum tolerated dose (MTD). Secondary objectives included determining the toxicity profile, objective response rate (ORR), median progression‐free survival (PFS), and overall survival (OS). Results: Twenty‐one patients were enrolled, 13 during dose escalation and 8 at the MTD. The median age was 66 years, 62% were female, 95% had stage IV disease, and 67% had received at least one prior line of therapy. The primary objective to establish the MTD was achieved at doses of ipilimumab 3 mg/kg and gemcitabine 1, 000 mg/m 2 . The most common grade 3 or 4 adverse events were anemia (48%), leukopenia (48%), and neutropenia (43%). The ORR was 14% (3/21), and seven patients had stable disease. Median response duration for the three responders was 11 months, with one response duration of 19.8 months. Median PFS was 2.78 months (95% confidence interval [CI], 1.61–4.83 months), and median OS was 6.90 months (95% CI, 2.63–9.57 months). Conclusion: Gemcitabine and ipilimumab is a safe and tolerable regimen for PDAC with a similar response rate to gemcitabine alone. As in other immunotherapy trials, responses were relatively durable in this study. Implications for Practice: Gemcitabine and ipilimumab is a safe and feasible regimen for treating advanced pancreatic cancer. Although one patient in this study had a relatively durable response of nearly 20 months, adding ipilimumab to gemcitabine does not appear to be more effective than gemcitabine alone in advanced pancreatic cancer. Abstract : Treatment of pancreatic ductal adenocarcinoma remains challenging because of its advanced presentation and resistance to chemotherapy and immunotherapy. This article reports results of a clinical trial of CTLA‐4 blockade with ipilimumab in combination with gemcitabine in patients with advanced pancreatic cancer, including maximum tolerated doses for the combination, safety data, and the antitumor activity observed in this trial.